(410) Educational Statistics & The Educational Plan in the U.A.R الإحصاء التربوي والخطة التعليمية في الجمهورية العربية المتحدة - Hamza, M. (معهد التخطيط القومى, 2024)
The study entitled “Educational Statistics and the Educational Plan in the U.A.R.” examines the role of educational statistics in developing educational plans and supporting national development strategies. The significance of the study lies in the argument that effective educational planning depends heavily on the availability of reliable quantitative data concerning student enrollment, admission rates, dropout patterns, population growth, and future labor-market requirements. The study emphasizes that educational systems cannot be efficiently managed or directed toward development objectives without a well-organized statistical framework capable of supporting decision-making processes. The study aims to establish a methodological framework for utilizing educational statistics in estimating future educational requirements and linking them to broader economic and social development goals. It further seeks to analyze the relationship between population growth and the expansion of compulsory education while identifying the requirements necessary for providing schools, teachers, and educational resources capable of accommodating future increases in student numbers. The analysis relies on statistical techniques and demographic forecasting methods to estimate future demand for educational services across different educational stages. Data on admission rates, age distribution, and participation rates are employed to determine the size of target groups eligible for compulsory education. Particular emphasis is placed on primary education as the foundational stage for educational planning. The findings suggest that successful educational planning depends strongly on the accuracy of statistical information used in forecasting future needs. The study also indicates that educational expansion requires coordination among educational policies, human-resource planning, and economic capacities. Furthermore, the analysis demonstrates that the use of reliable statistical indicators can reduce the gap between expected educational demand and institutional capacity. The study contributes by providing a practical framework that assists policymakers and educational planners in designing more efficient educational policies aligned with long-term economic and social development goals.